Reconstruction of a rare variant of the left hepatic vein in a left lateral segment liver graft from a living donor: Technical notes - Fadl H Veerankutty; T.U. Shabeer Ali; Krishnan Sarojam Manoj; B Venugopal (Wolters Kluwer Medknow Publications, 2016)
Reconstruction of hepatic veins in living donor liver transplantation (LDLT) is often technically challenging and a good venous outflow is essential for survival of the graft and patient. We describe a quadrangular patch venoplasty technique used for the reconstruction of a rare variant of the left hepatic vein (LHV) in a pediatric LDLT with left lateral segment (LLS) graft. Segment II vein in the graft was draining directly into the inferior vena cava (IVC) and segment III vein was draining into the middle hepatic vein (MHV) after receiving a tributary from segment IV so that there were two widely separated ostia at the cut surface. This is one of the rarest variations of the LHV and is so called type 3 variant; it is usually reconstructed using interposition tubular conduits necessitating two separate anastomoses at the IVC.